ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP MARKET VALUE ADDED (MVA) PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sunarko, Bambang; Martini, Sri (Faculty of Economics and Business Universitas Jenderal Soedirman, 2011)
This research is an empirical study to analyze the data causally (cause and effect). This research entitled by: